Sanksi Administratif dan Pidana dalam Hukum Kearsipan terhadap Pelanggaran Prosedur Migrasi dan Alih Media Arsip Vital - gita khairunisa (Jurnal Hukum Lex Generalis, 2026)
This normative-juridical study analyzes the legal liability of archival officials and third parties for procedural violations in the migration and media transfer of vital electronic archives. Article 78 of Law No. 43 of 2009 establishes graduated administrative sanctions: written reprimand, deferral of salary increment and deferral of promotion for negligent officials (culpa). Article 79 governs dismissal from office where no corrective action is taken. Article 85 imposes a maximum criminal penalty of five years imprisonment or a fine of Rp250,000,000 for perpetrators acting with deliberate intent (dolus). The absence of technical implementing regulations constitutes the primary gap undermining effective prosecution of violations. ANRI must promptly issue a Head of ANRI Regulation encompassing digital audit trail SOPs, vendor certification and a graduated sanctions mechanism as a binding accountability instrument.